Evaluation of rice tolerance and weed control with acetochlor and fenclorim. (3rd December 2022) - Avent, Tristen H.; Norsworthy, Jason K.; Butts, Thomas R.; Roberts, Trenton L.; Bateman, Nicholas R.
Abstract: Many problematic weeds have evolved resistance to herbicides in mid-southern U.S. rice fields. With the lack of new effective herbicides, rice producers seek alternatives that are currently not labeled for rice production. Inhibitors of very-long chain fatty acid elongase (VLCFA) are currently not labeled for use with U.S. rice crops but are labeled for use in other U.S. row cropping systems and rice production in Asia. Previous research has demonstrated the utility of VLCFA inhibitors for weed control in rice; however, these herbicides induce variable amounts of injury to the crop when applied early in the growing season. Experiments were initiated in 2020 and 2021 at the Rice Research and Extension Center near Stuttgart, AR, to evaluate rice tolerance and weed control with acetochlor and seed treatment with a herbicide safener, fenclorim. Three rates of a microencapsulated formulation of acetochlor (630, 1, 260, and 1, 890 g ai ha −1 ), four application timings (preemergence, PRE; delayed-preemergence, DPRE; spiking; and 1-leaf), and without or with the fenclorim seed treatment (2.5 g kg −1 of seed) were used to evaluate rice tolerance, weedy rice control, and barnyardgrass control. Acetochlor applied DPRE at 1, 260 g ai ha −1 provided better weedy rice and barnyardgrass control than applications at the 1-leaf stage at the same rate. Acetochlor rates of 1, 260 and 1, 890 g ai ha −1 reduced barnyardgrass and weedy rice densities by more greater than the 630 g ai ha −1 rate. The fenclorim seed treatment did not influence weedy rice or barnyardgrass control but did reduce injury for DPRE acetochlor applications. Based on these results, acetochlor can be safely applied to rice DPRE (≤19% injury) at 1, 260 g ai ha −1 when the seed is treated with fenclorim, leading to ≥88% barnyardgrass and ≥45% weedy rice control 28 d after treatment.